Analysis of the Damage of Boiler Bottom Slope Pipe in Steam Power Plant - Rusnaldy, Rusnaldy (University of Muhammadiyah Malang, 2016)
Bottom slope pipe on boiler system in one of steam turbine power plant had been damaged. The damage was dent on the outside of pipe and was suspected as a result from foreign object impact from outside pipe. From chemical composition examination and hardness test, it showed that nothing wrong with the selection of the pipe. From visual inspection, there is no other factor such as corrosion or deposit formed inside the pipe was found. Analysis of cause of damage in the pipe then further conducted by observing microstructure and hardness value on the area which experience damage. Simulation on mechanical and thermal analysis had been conducted to determine what and origin of foreign object which impacted on pipe and the temperature when it was happened. From the observation, of microstructure and hardness test showed that pipe had been experience plastic deformation on temperature under recrystallization temperature. Simulation results also confirmed that the initial assumption on cause of pipe damage from foreign object, which is small size slag that felt from very high location so that caused high speed impact on pipe. Thermal analysis result also supporting the suspicion that slag impact on pipe was occurred in temperature under recrystallization of pipe material.